A Fuzzy Based Grid Maintenances and Load Balancing Technique for Feature Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a Mobile Ad Hoc Network, this article suggests a Fuzzy dependent power scheduling and load balancing strategy for ZRP (MANET). The duty-cycles of border nodes are adaptively modified using this method, which takes into account the queue condition, expected residual capacity, and distance to border nodes. The nodes are active throughout each round and then go into sleep mode depending on the calculated duty-cycle time. When the load reaches a certain threshold, the zone leaders (ZL) are updated adaptively.